THE DESCRIPTION OF MULTIMEDIA VOCITAS AS AN INTEGRATIVE UNIT FOR IMPROVING THE SOCIAL PEDAGOGICAL ACTIVITY OF STUDENTS (American Journal of Interdisciplinary Research and Development, 2023)
In this article, the improvement of the socio-pedagogical activity of students in Multimedia Voices is described as an integrative unit in the process of socialization of students and factors.